Skip school, fly to space : a Pearls before swine collection - Pastis, Stephan (Andrews McMeel Pub., LLC, 2015)
A new collection of "Pearls Before Swine" comic strips specifically chosen for younger readers, featuring the adventures of know-it-all Rat, slow-witted Pig, and their animal friends.